Comparisons of sea ice motion and deformation, and their responses to ice conditions and cyclonic activity in the western Arctic Ocean between two summers - Lei, R; Gui, D; Heil, P; Hutchings, JK; Ding, M (Cold Regions Science and Technology, 2019)
Measurements from 30 and 31 ice drifters during the seasonal transition from mid-August to late September of 2014 and 2016, respectively, were used to characterize sea ice motion and deformation in the western Arctic Ocean. The dispersion distance for the ice deformation in summer was markedly reduced because the mechanical behavior of sea ice in summer is closer to free drift and more granular compared to that in winter. For unconsolidated sea ice in late summer the logarithmic relationship between deformation and spatial scale is 2.43.1 times that for ice under freezing conditions. For 2007 to 2016 late summer (August September) sea ice compactness in the Arctic was the highest (lowest) in 2014 (2016). Along the trajectories of the 2016 (2014) ice camp, the average 10-m wind speed in AugustSeptember was larger (smaller) than that averaged in 19792016 by 20% (13%). Relative to the great Arctic cyclone in August 2012, cyclones in summer 2016 had comparable sizes and intensity but with longer persistence. Lower ice compactness coupled with stronger cyclonic activity in late summer 2016 led to increased ice speed and enhanced deformation compared to 2014. Sea ice during late summer 2016 was closer to free drift, resulting in greater homogeneity of the drift field, a larger icewind speed ratio, as well as weaker multifractality, localization, and spacetime coupling of the deformation field compared to late summer 2014. The localization of ice deformation in late summer 2014 was comparable to that obtained in the freezing season because of the high ice compactness. The enhanced ice dynamics in summer 2016 promoted ice melt and area loss via the positive albedo feedback.